Thermal energy storage based on cold phase change materials: Charge phase assessment. (25th November 2022) - Reboli, Tommaso; Ferrando, Marco; Traverso, Alberto; N.W. Chiu, Justin
Highlights: Experimental study of water–ice energy storage behavior at density inversion temperature. Experimental analysis of a finned shell & tube latent heat thermal energy storage. Effect of temperature, mass flow rate and charge direction on storage performance. Presence of metastable phase is confirmed. Abstract: Integration of thermal energy storage in energy systems provides flexibility in demand–supply management and in supporting novel operational schemes. In a combined heat and power cycle, it has been shown that integration of cold thermal energy storage is beneficial to fine-tune electric power and heating/cooling production profiles to better match the load demand. Latent heat storage systems have the advantage of compactness and low temperature swing, however storage performance analysis on large scale setup operating around the density inversion temperature is still limited. In this work, a shell & tube, latent heat based cold thermal energy storage was studied around the density inversion temperature of ice-water at 4 °C and the performance was characterized. Sensitivity analyses on heat transfer fluid flow rate, flow direction and inlet temperature were performed. The results show 27% power increase with doubled mass flow and 18% shorter charge time with 2 °C lower charge temperature. Contrary to general expectations during solidification, the cold thermal energy storage actually shows between 5% and 6% better thermal performance and reducing instant icing power jump of 36% due to supercooling with downwards cold heat transfer fluid flow in cooling charge cycle due to buoyancy change around density inversion temperature. This fact highlights the importance of accounting for the buoyancy effect due to density inversion when designing the operational schemes of large size cold thermal energy storage.